Portrayal of the Human Resource Crisis and Accountability in Healthcare: A Qualitative Analysis of Ugandan Newspapers - Wojczewski, Silvia; Willcox, Merlin; Mubangizi, Vincent; Hoffmann, Kathryn; Peersman, Wim; Niederkrotenthaler, Thomas; Natukunda, Silvia; Maling, Samuel; Maier, Manfred; Mant, David; Kutalek, Ruth (PLoS One, 2015)
Uganda is one of the 57 countries with a critical shortage of health workers. The aim of this study was to determine how the human resources and health service crisis was covered in Ugandan newspapers and, in particular, how the newspapers attributed accountability for problems in the health services. Methods We collected all articles related to health workers and health services for the calendar year 2012 in the two largest national newspapers in Uganda (collection on daily basis) and in one local newspaper (collection on weekly basis). These articles were analysed qualitatively regarding the main themes covered and attribution of accountability. Results The two more urban national newspapers published 229 articles on human resources and health services in Uganda (on average over two articles per week), whereas the local more rural newspaper published only a single article on this issue in the 12 month period. The majority of articles described problems in the health service without discussing accountability. The question of accountability is raised in only 46% of articles (106 articles). The responsibility of the government was discussed in 50 articles (21%), and negligence, corruption and misbehaviour by individual health workers was reported in 56 articles (25%). In the articles about corruption (n=35), 60% (21 articles) mention corruption by health workers and 40% (14 articles) mention corruption by government officials. Six articles defended the situation of health workers in Uganda. Conclusions The coverage of accountability in the Ugandan newspapers surveyed is insufficient to generate informed debate on what political actions need to be taken to improve the crisis in health care and services. There exists not only an “inverse care law” but also an “inverse information law”: those sections of society with the greatest health needs and problems in accessing quality health care receive the least information about health services.
Keywords: Human Resource Crisis; Healthcare; Ugandan Newspapers